ANALISIS PENERIMAAN APLIKASI UBERSOCIAL DENGAN MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL DI JURUSAN ILMU KOMUNIKASI UNIVERSITAS RIAU - Dede Putra; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Many implementations adaptation of information systems failure caused not due to technical factors but more on the human factor. Some research suggests that a system of user behavior information and social media have an important role to the success of its implementation. UberSocial is a third party application on social networks Twitter and Facebook, answering the challenges of social media users who want a process of information exchange in the form of text, images or videos become easier to use and faster. These applications provide more convenience to the user to be able to use multiple social media accounts at the same time with just one app UberSocial. This study aimed to examine the effect among variables at the Technology Acceptance Model UberSocial app.Respondents in this study were 105 UberSocial app users in the Department of Communication Studies, University of Riau. How to determine the number of samples using unknown population due to the lack of valid data on the number of users of the application UberSocial. Use traditional methods of data collection questionnaire. Data were analyzed using Sructural Equation Model (SEM) with AMOS and SPSS software program. Based on the literature review, the research model using the Technology Acceptance Model (TAM) with variable perceived ease of use, perceived usefulness, attitude toward using and acceptance.The results of this study indicate the variables perceived ease of use has a positive and significant effect on the variable attitude toward using the total influence of 0.292. Variable perceived ease of use has a positive and significant effect on the variable acceptance by the effect of a total of 0.720. Variable perceived usefulness has a negative influence on attitude toward using variable and has a total effect of 0.237. Variable perceived usefulness has a negative influence on the variable acceptance. Variable attitude toward using has a positive effect on the variable acceptance.Key Word: UberSocial, Technology Acceptance Model (TAM), Structural Equation Model (SEM)